2014
DOI: 10.1159/000364860
|View full text |Cite
|
Sign up to set email alerts
|

Acne Pathogenesis: History of Concepts

Abstract: From the first reliable descriptions of acne in the early 19th century, dermatologists recognized it as a disease of the pilosebaceous follicle. Until the middle of the 20th century, they hypothesized that seborrhoea, follicular keratosis and microorganisms could be individually responsible for the acne lesions. Inflammation was only regarded as the final and inescapable step of the acne process. Although the importance of these factors has been reevaluated, recent works still regarded them as mandatory. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 246 publications
(345 reference statements)
0
17
0
1
Order By: Relevance
“…Given the crucial role of hormones in the pathogenesis of acne, therapies with antiandrogenic or antisebogenic properties are mechanistically enticing options. [31][32][33][34][35] Spironolactone is a synthetic 17-lactone steroid that has antagonistic effects on the androgen and progesterone receptors. Although its original clinical application was as a potassiumsparing diuretic, due to its impact on sebum production through inhibition of the androgen receptor on sebocytes, spironolactone has been used off-label in the treatment of acne for over 30 years.…”
Section: Spironolactonementioning
confidence: 99%
“…Given the crucial role of hormones in the pathogenesis of acne, therapies with antiandrogenic or antisebogenic properties are mechanistically enticing options. [31][32][33][34][35] Spironolactone is a synthetic 17-lactone steroid that has antagonistic effects on the androgen and progesterone receptors. Although its original clinical application was as a potassiumsparing diuretic, due to its impact on sebum production through inhibition of the androgen receptor on sebocytes, spironolactone has been used off-label in the treatment of acne for over 30 years.…”
Section: Spironolactonementioning
confidence: 99%
“…Nagler et al ( 2016 ) reported that the average duration of antibiotic therapy in acne in some cases may even exceed 1 year (Nagler et al, 2016 ). Such prolonged therapy can be shortened by the addition of isotretinoin (a 13-cis-retinoic acid which is a non-aromatic retinoid; Tilles, 2014 ), whose action is associated with reduction of sebum production, anti-inflammatory properties, reduction in P. acnes and an effect on comedogenesis (decreasing hyperkeratinization; Layton, 2009 ). Isotretinoin is used to treat severe and recalcitrant cases of inflammatory acne.…”
Section: Conventional Treatment Of Acnementioning
confidence: 99%
“…Acne vulgaris is a disease of the pilosebaceous unit with four pathogenic factors, including abnormal keratinization, increased sebum production, Propionibacterium acnes (P acnes) colonization, and inflammation. 1,2 Treatment of acne is based on its severity, which is broadly classified into mild, moderate, and severe forms. In mild disease, topical regimens such as retinoids, antibiotics, and benzoyl peroxide are the cornerstones of treatment, while systemic therapies are considered in patients with moderate to severe disease.…”
Section: Introductionmentioning
confidence: 99%